Serum resistin levels may be new prognostic factor of crimean-congo hemorrhagic fever - Erturk, Ayse (Int J Clin Exp Med, 2014)
Crimean-Congo hemorrhagic fever (CCHF) virus can cause potentially fatal infections in humans. During this disease, cytokines are intensive released. Resistin which is a good marker of inflammation is an adipocytokine released from adipose tissue. We aimed to investigate whether serum resistin level in patients with CCHF has a prognostic value in predicting recovery time. Twenty men and 22 women (a total of 42 CCHF patients) and a similar age group of 40 healthy individuals (16 men and 24 women) were included in the study. Hematologic tests, serum resistin level, C-reactive protein (CRP) and others biochemical values of all the two group subjects were evaluated. Multivariate logistic regression analysis was performed. Resistin level of patients with CCHF was higher than the controls (1252.6±864.7 ng/ml vs. 824.1±224.6 ng/ml, p=0.003). There was strongly association among recovery time, increased resistin level (p < 0.001), prothrombin time (PT) (p < 0.001), INR (p < 0.001), decreased white blood cell count (WBC) (p=0.012) and lower platelet counts (p=0.007). Serum resistin level is significantly elevated in CCHF patients. Resistin level may be a good prognostic factor to predict recovery time in patients with CCHF.